Analisis Pembentukan Ryakugo pada Majalah Fashion Jepang: Studi Perbandingan Antara Majalah Pria dan Wanita - Nurjaleka, Lisda; Azhimal, Jihad Fauzan (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2024)
One of the word formation processes in Japanese is shouryaku or word shortening. Word shortening is often used in daily communication in Japanese society. In Japanese, the result of shortening a word is called ryakugo. Ryakugo is a new vocabulary that is formed after undergoing a word shortening process by removing several syllables from the original word. The purpose of this study was to describe the types and processes of ryakugo formation in the August 2021 edition of Japanese men's and women's fashion magazines. The fashion magazines used as data sources are Men's Non-no, Begin, Non-no, and Jelly magazines. The results of this study was founded 65 pieces of ryakugo vocabulary with a total frequency of occurrence of 283 times in the data source. The fashion magazine with the highest frequency of ryakugo appearances is the women's fashion magazine with 182 appearances, while the men's fashion magazine ryakugo appeared 101 times. The type of ryakugo that is most often found in the four Japanese fashion magazines is the koubu shouryakukei type and the process of forming the ryakugo that is most widely used is the process of shortening the ends (geryaku).